Synthesis and biological evaluation of novel isothiazoloquinoline quinone analogues. Issue 16 (15th August 2020) - Chen, Ling; Xie, Yuan-Zhu; Luo, Zhi-Yong; Liu, Li-Jun; Zou, Zi-Zheng; Liu, Hong-Dou; Kong, Fan-Rong; Hao, Ying; Gao, Jin-Lei; Wang, Liu-Liu; Ma, Da-You; Liu, Su-You
Graphical abstract: Highlights: A series of unique isothiazole-fused quinolinoquinone analogues were synthesized. Some isothiazoloquinolinoquinones strongly inhibit proliferation of cancer cells and may induce cancer cells apoptosis. Isothiazoloquinolinoquinones are efficient substrates for NQO1 and induce ROS production in vitro . Isothiazoloquinolinoquinone inhibits the phosphorylation of STAT3. Abstract: Natural quinones and their analogues have attracted growing attention because of their novel anticancer activities. A series of novel isothiazoloquinoline quinone analogues were synthesized and evaluated for antitumor activities against four different kind of cancer cells. Among them, isothiazoloquinolinoquinones inhibited cancer cells proliferation effectively with IC50 values in the nanomolar range, and isothiazoloquinolinoquinone 13a induced the cell apoptosis. Further exploration of possible mechanism of action indicates that 13a not only activates ROS production through NQO1-directed redox cycling but also inhibits the phosphorylation of STAT3. These findings indicate that 13a has potential use for the development of new skeleton drug candidate as an efficient substrate of NQO1 and STAT3 inhibitor.